ANALISIS TEKNIK MEMAHAMI PERKEMBANGAN PESERTA DIDIK SEKOLAH DASAR GMIT 027 MEBUNG - Doni Rian Putra Beri; Evi Fania Panduwal, Harun Letmani, Yessy Mata, Petrus Mau Tellu Dony, Jon Abraham Lalang Yame (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
The purpose of this study is to examine the techniques used to understand the development of students at GMIT 027 Mebung Elementary School in Alim Mebung Village, Alor Tengha Utara Subdistrict, Alor Regency. The research technique used in this study was qualitative descriptive, interviews with the homeroom teacher of class IIIA, Mrs. Rosalina H. Doeka, S.Pd, together with the students of class IIIA at GMIT 027 Mebung Elementary School, Alim Mebung Village, Alor Tengha Utara District, Alor Regency. The results of this study indicate that teachers have applied and used techniques in understanding student development, although they have also felt the impact of the techniques used by teachers, although not all of them have been felt at GMIT 027 Mebung Elementary School, especially in class IIIA.